PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI METODE "READING THEATRE" PADA SISWA KELAS VI SD NEGERI KALUKUANG KECAMATAN BAROMBONG KABUPATEN GOWA - Sitti Nurul Fauziah; Anin Asnidar; Ratnawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve students’ reading comprehension through the application of the Reading Theatre method. The research employed Classroom Action Research consisting of two cycles conducted with 27 sixth-grade students of SD Negeri Kalukuang, Gowa Regency. Each cycle included planning, action, observation, and reflection stages. Data were collected through observation and reading comprehension tests. The results showed an improvement in students’ reading comprehension achievement. In Cycle I, 17 students (62.96%) achieved the minimum mastery criteria, while in Cycle II, the number increased to 23 students (85.19%). These findings indicate that the Reading Theatre method effectively improves reading comprehension skills of sixth-grade students.